1985
DOI: 10.1111/j.1471-0528.1985.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal umbilical artery flow velocity waveforms and placental resistance: pathological correlation

Abstract: Placental microvascular anatomy was correlated with antenatal assessment of the umbilical circulation in 106 patients to further validate the measurement of the A/B ratio (the ratio of peak systolic to least diastolic flow velocity) of the umbilical artery flow velocity time waveforms as an index of' blood flow resistance. Three groups of patients were studied: a normal group of 38 uncomplicated pregnancies, a control group of 33 potentially 'at risk' pregnancies with a normal A/B ratio matched by risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
223
1
13

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 705 publications
(247 citation statements)
references
References 18 publications
10
223
1
13
Order By: Relevance
“…6 Once 60-70% of the vasculature is affected, absent or reversed end diastolic flow results. 7 Reversed end diastolic flow is an ominous finding and is associated with a high mortality rate within 1-7 days if fetus is left in utero.…”
Section: Introductionmentioning
confidence: 99%
“…6 Once 60-70% of the vasculature is affected, absent or reversed end diastolic flow results. 7 Reversed end diastolic flow is an ominous finding and is associated with a high mortality rate within 1-7 days if fetus is left in utero.…”
Section: Introductionmentioning
confidence: 99%
“…Placental dysfunction can result in insufficient fetal nutrition, which can lead to intrauterine growth restriction (IUGR) [2][3][4][5][6]. At least 8% of human pregnancies end in infant death due to complications that arise from IUGR [1;7;8].…”
Section: Introductionmentioning
confidence: 99%
“…Pathological studies have demonstrated that increased impedance in the umbilical arteries becomes evident only when at least 60% of the placental vascular bed is obliterated (12) . Clinical studies of umbilical arterial flow velocity waveforms in intrauterine growth restriction have reported progressive increase in impedance to flow until absence and, in extreme cases, reversal of end-diastolic frequencies (13) .…”
Section: Umbilical Arteriesmentioning
confidence: 99%